2015
DOI: 10.1142/s0192415x15500779
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Products for Ischemic Stroke

Abstract: Traditional Chinese herbal products (CHPs) have been described in ancient medicine systems as treatments for various stroke-associated ailments. This study is aimed to investigate the prescription patterns and combinations of CHPs for ischemic stroke in Taiwan. Prescriptions of CHPs for ischemic stroke were obtained from the National Health Insurance Research Database (NHIRD) of Taiwan. Every prescription with a leading diagnosis of ischemic stroke made during 2000-2010 was analyzed. Descriptive statistics wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…Dan Shen was the most commonly prescribed single CHP for ischemic stroke (16.50%), and Shi Chang Pua with Yuan Zhi was the most commonly prescribed single-CHP combination (4.79%). These results provide information about individualized stroke therapy and propose specific CHP components and formulas for further pharmacological investigation and clinical evaluation [16].…”
Section: Bu-yang-huan-wu-tang (Byhwt) and Dan Shenmentioning
confidence: 84%
“…Dan Shen was the most commonly prescribed single CHP for ischemic stroke (16.50%), and Shi Chang Pua with Yuan Zhi was the most commonly prescribed single-CHP combination (4.79%). These results provide information about individualized stroke therapy and propose specific CHP components and formulas for further pharmacological investigation and clinical evaluation [16].…”
Section: Bu-yang-huan-wu-tang (Byhwt) and Dan Shenmentioning
confidence: 84%
“…Insomnia and depression In 2002∼2010, 37% of patients diagnosed with insomnia used hypnotic drug and herbal medicine in combination 53) In 2003, 42.73% of patients with major and mild depressive disorder who were prescribed antidepressant used TEAM 54) In 64,65) In 2008, The acupuncture utilization rate of stroke patients increased to 17% 66) In 2000, 24% of stroke patients used TEAM, but in 2009, they increased to 32% 67) In 2000∼2010, 77.30% of newly diagnosed ischemic stroke patients used TEAM 68) Atrial fibrillation In 2000∼2011, 15.35% of newly diagnosed atrial fibrillation patients used TEAM within 7 days 69) Heart failure In 2001∼2010, 78.50% of newly diagnosed heart failure patients used TEAM 70) Ischemic heart disease In 2000∼2010, 81.59% of newly diagnosed ischemic heart disease patients used TEAM 71) Diseases of the respiratory system (7.53%)…”
Section: 대만의 보편적 Team 이용 관련 연구mentioning
confidence: 99%
“…Buyang Huanwu decoction (BYHWD) is the most frequently prescribed formula for stroke treatment (40.32%) [14]. Evidence-based investigations have found that BYHWD improves neurological deficiencies in both experimental studies and clinical trials [15-17].…”
Section: Introductionmentioning
confidence: 99%